Why sinonasal disease spares the inferior turbinate: An immunohistochemical analysis. (24th November 2015) - White, Lauren C.; Weinberger, Paul; Coulson, Hannah; Guo, Dehuang; Jang, David; Gurrola, Jose; Kountakis, Stilianos E.
Abstract : Objectives/Hypothesis: Clinically, inflammatory polyps are found in the middle turbinate (MT) in patients with chronic rhinosinusitis (CRS) but not in the inferior turbinate (IT). The purpose of this study was to investigate differences in protein expression between IT and MT tissue in patients with CRS. Study Design: Prospective cohort. Methods: Pathologic specimens obtained from patients with CRS undergoing functional endoscopic sinus surgery with IT reduction were evaluated by immunohistochemical analysis of inflammatory markers cysteinyl leukotriene 1 receptor (CysLT1R), toll‐like receptor 2 (TLR2), and vascular cell adhesion molecule 1 (VCAM1). Protein expression was quantified with nuance multispectral analysis and results compared between MT and IT tissue. Results: The total expression of VCAM1 and CysLT1R was decreased in the IT compared to the MT. There was no difference in total TLR2 expression between the IT and MT. When comparing patients with eosinophilic CRS to noneosinophilic CRS (neCRS), there was decreased expression of VCAM1 in the IT of patients with neCRS. When comparing patients with nasal polyposis to those without polyps, there was decreased expression of VCAM1 in the IT of patients without polyps. Conclusions: There is a difference in protein receptor expression of VCAM1 and CysLT1R in MT compared to IT tissue. Although the leukotrienes are a well‐known target for treatment of chronic sinusitis, this is the first study demonstrating an upregulation of VCAM1 expression in the MT and could be a potential future target for the treatment of CRS. Level of Evidence: NA Laryngoscope, 126:E179–E183, 2016